Nanospheres from polymerized lipofullerenes - Hetzer, Michael; Clausen-Schaumann, Hauke; Bayerl, S.; Bayerl, Thomas; Camps, Xavier; Vostrowsky, Otto; Hirsch, Andreas (Angewandte Chemie International Edition, 1999)
Remarkably mechanically stable spherical nanostructures are formed by UV-initiated polymerization from polymerizable lipofullerene 1 in multilamellar lipid vesicles. The polymer beads can be filled or hollow. R=COO(CH ) C ≃ C-C ≃ C(CH ) CH .